Electronic defect study on low temperature processed Cu(In, Ga)Se2 thin-film solar cells and the influence of an Sb layer. (27th March 2015) - Van Puyvelde, L; Lauwaert, J; Tempez, A; Devulder, W; Nishiwaki, S; Pianezzi, F; Detavernier, C; Tiwari, A N; Vrielinck, H
Abstract: A way to lower the manufacturing cost of Cu(In, Ga)Se2 (CIGS) thin-film solar cells is to use flexible polymer substrates instead of rigid glass. Because such substrates require lower temperature during absorber deposition, the grain growth of the absorber layer can be hindered which leads to a lower cell performance. Partial compensation of this efficiency loss might be accomplished by growing the absorber in the presence of Sb, which is reported to promote grain growth. In this work CIGS solar cells, deposited on glass substrates, at a reduced substrate temperature with a thin Sb layer (7, 12 nm) on top of the Mo contact are investigated. The diffusion profile of Sb is measured with plasma profiling time of flight mass spectrometry. The beneficial effect of Sb on efficiency and grain size is shown in quantum efficiency measurements and with scanning electron microscopy, respectively. Electric spectroscopy is used to explore the possible effects on the defect structure, more in particular on the dominant shallow acceptor. Admittance spectra exhibit a capacitance step to the geometric capacitance plateau at low temperature (5–60 K). Analyzing this capacitance step, we obtained a good estimate of the activation energy of the intrinsic defects that provide the p -type conductivity of the CIGS absorber. The measurements did not show a change in the nature of the dominant acceptor upon Sb treatment.